Comparison of fertilization, hatching, and survival rates in Clarias gariepinus x Clarias macrocephalus hybrid exposed to thermal shocks. - Escorpion, Carmela Vargas
Catfish is considered as one of the world's most important fish in aquaculture. The freswater catfish Clarias macrocpehalus is native to the Philippines and has a tender and delicious meat. Recently, farming of C. macrocephalus has gained interest among catfish growers. However, this species is fast becoming scarce due to its slow growth and poor breeding activities. This led to the introduction of exotic and faster growing secies like the African catfish; C. gariepinus and Thai catfish, C. batrachus. Hybrids of C. macrocephalus and C. gariepinus are viable for aquaculture., This special problem was conducted to compare performance in hybrids produced from Clarias gariepinus x Clarias macrocephalus cross and to specifically compare their fertilization, hatching and larval survival rates at 7 days post-hatching. Coldshock treatments of artificially fertilized eggs were done for 30 minutes duration at 5 degrees, 7 degrees and 9 degrees centigrade while heatshock were carried out at 34 degrees, 37 degrees and 39 degrees centigrade for 3.5-4 minutes. Based on experimental results, C. gariepinus x Clarias macrocephalus female hybrids have better performance than C. gariepinus female x C. macrocephalus male hybrids as determined by numerical data such as percent fertilization, hatching and survival. Higher values on these parameters were obtained in heatshock treatments than in coldshock treatments. The temperature suitable for better hybrid survival is between 34 degrees - 39 degrees centigrade.